2020
DOI: 10.1001/jamapsychiatry.2019.2905
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of Sex-Specific Suicide Risk Using Machine Learning and Single-Payer Health Care Registry Data From Denmark

Abstract: IMPORTANCE Suicide is a public health problem, with multiple causes that are poorly understood. The increased focus on combining health care data with machine-learning approaches in psychiatry may help advance the understanding of suicide risk.OBJECTIVE To examine sex-specific risk profiles for death from suicide using machine-learning methods and data from the population of Denmark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 61 publications
(117 reference statements)
4
113
0
1
Order By: Relevance
“…60,61 Still other machine-learning studies developed a large number of synthetic or compound potential suicide risk factors (for example alcohol use by various age and gender groups) increasing the risk of chance associations. 46,97 We conclude that the case for machine learning as a statistically superior method of suicide prediction model is not yet conclusive.…”
Section: Discussionmentioning
confidence: 89%
“…60,61 Still other machine-learning studies developed a large number of synthetic or compound potential suicide risk factors (for example alcohol use by various age and gender groups) increasing the risk of chance associations. 46,97 We conclude that the case for machine learning as a statistically superior method of suicide prediction model is not yet conclusive.…”
Section: Discussionmentioning
confidence: 89%
“…These results call for more research in the timing of diagnoses of psychiatric disorders and the use of psychotropic medications in relation to suicidal behavior. Using the Danish registry data, a recent study predicting sex-specific suicide risk reported that diagnoses occurring long (e.g., 48 months) before suicide were more important for suicide prediction than diagnoses occurring shortly (e.g., 6 months) before suicide [ 41 ]. Since the authors defined the predictors using time of suicide, which could not be known beforehand, the models would not be implementable in clinical systems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 47% of crack-cocaine users had a current suicide risk [14], and a prevalence of suicidal behaviors of 30% in crack-cocaine addicts, in Brazil. The subject of suicide has been the focus of studies in psychiatry in the last decades, but the understanding about this behavior remains insufficient [15]. Moreover, the predictive factors in this vulnerable population were not well explored yet.…”
Section: Introductionmentioning
confidence: 99%